The role of antigen presentation in the ontogeny of immune responses to herpes simplex virus. - Howie, S E (1988)
The ability of epidermal antigen presenting cells (APC) to induce immune responses to herpes simplex virus (HSV) has been studied in mice of differing ages. Using an in vivo model of HSV infection we have demonstrated that neonatal epidermal cells (EC) induce specific suppression of DH to HSV in normal syngeneic adult mice. The suppression is transferable and mediated by T cells of the Lyt1+, Lyt2-, L3T4+ phenotype. The ability of EC to induce suppression persists up to 4 weeks of age, whereas EC from mice 6 weeks of age or older induce positive DH responses to the virus. This correlates with the susceptibility of mice of the different ages to HSV infection and their ability to mount DH responses to the virus.